Bridging the Therapeutic Gap: A Systematic Review and Meta-Analysis on the Efficacy, Safety, and Pathophysiological Impact of Sodium Zirconium Cyclosilicate in Enabling Guideline-Directed Medical Therapy - Edy Nur Rachman; Ian Effendi; Zulkhair Ali; Novadian; Suprapti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Hyperkalemia is a life-threatening complication of chronic kidney disease (CKD) and heart failure (HF), primarily impeding the use of life-saving renin-angiotensin-aldosterone system inhibitors (RAASi). This systematic review and meta-analysis evaluate the evidence for sodium zirconium cyclosilicate (SZC) in managing hyperkalemia and enabling RAASi therapy. Methods: This systematic review searched Medline, Embase, and Cochrane CENTRAL to September 2025. Dual reviewers independently screened, extracted data, and assessed bias (Cochrane RoB 2, Newcastle-Ottawa Scale). We included RCTs and observational studies of SZC in adults with hyperkalemia. A random-effects meta-analysis was performed on RCTs reporting maintenance-phase efficacy and safety. Results: The search yielded 1,254 citations, with 6 pivotal studies included. The meta-analysis of 3 RCTs found that SZC (5-10g daily) was significantly more effective than placebo at maintaining normokalemia over 12-28 days. The pooled mean difference in serum K+ was -0.58 mEq/L (95% CI: -0.65 to -0.51; I2 = 0%). SZC did increase the risk of edema (pooled Risk Ratio: 2.95; 95% CI: 1.51 to 5.76; I2 = 0%). The narrative synthesis of observational data confirmed that SZC use was associated with a >2.5-fold increase in the likelihood of continuing RAASi therapy. Conclusion: Sodium zirconium cyclosilicate is a highly effective and rapidly acting agent for both acute correction and chronic management of hyperkalemia. Our meta-analysis provides a precise estimate of its high maintenance-phase efficacy. Its primary clinical benefit lies in providing a renal-independent pathway for potassium excretion, thereby "uncoupling" potassium levels from RAASi use and bridging a critical treatment gap.